Single-Cell Transcriptomic Analysis of Peripheral Blood Reveals a Novel B-Cell Subset in Renal Allograft Recipients With Accommodation - Zhuang, Quan; Li, Hao; Peng, Bo; Liu, Yang; Zhang, Ying; Cai, Haozheng; Liu, Shu; Ming, Yingzi (Frontiers in Pharmacology, 2021)
Background: Kidney transplantation (KTx) is a preeminent treatment for end-stage renal disease (ESRD). After application of immunosuppressants (IS), renal allograft recipients could reach a state called accommodation which means they are neither rejected nor infected. This study aimed to describe the details of this immune accommodation and reveal novel mechanism of IS on immune cell subpopulations. Methods: We analyzed multiple cell subgroups and their gene expression of peripheral T, B, myeloid and NK cells from renal allograft recipients with accommodation and healthy control (HC) by single-cell transcriptomics sequencing (scRNA-seq) and flow cytometry. Results: A total of 8272 cells were isolated and sequenced from three individuals, including 2758 cells from HC, 2550 cells from ESRD patient and 2964 cells from KTx patient, as well as 396 immune response-related genes were detected during sequencing. 5 T cell, 4 NK cell, 5 myeloid and 4 B cell clusters were defined. Among then, a B cell subset (CD19+IGLC3lowIGKChighTCL1A-CD127+) of renal transplant recipients with accommodation was significantly lower than that of HC and verified by flow cytometry, and this B cell subset showed an activated potential because of its high expression of CD127. Furthermore, we found that IL32 might be the key cytokine to induce the differentiation of this B cell cluster. Conclusions: We found a novel B cell subset (CD19+IGLC3lowIGKChighTCL1A-CD127+) with was inhibited and decreased in renal allograft recipients with accommodation. This study might reveal the effect of commonly used IS in clinical practice on B cell subsets and related mechanism.